An overview of workflows for developing Geological Virtual Field Trips, limitations, and future implications: A case study from Peninsular Malaysia - Soto, G.J. (Slovnaft VURUP a.s, 2021)
Recent literature has demonstrated the importance of fieldwork in geology. However, as the pandemic of COVID 19 emerged since 2019, several issues have arisen to develop fieldwork experiences in several educational centers around the world, at the same time resources have become scarce, and field experiences are often targeted for cuts. In courses throughout, field trips and other excursions were postponed, making it so students do not have the opportunity to participate in geology field trips. In response, we have developed a virtual field experience (VFEs) from one of our nearby outcrops, Kinta Valley limestone to create a virtual reality (VR) model and 3D rock model based on available rock samples in our Laboratory at Universiti Teknologi Petronas. Â© 2021, Petroleum and Coal. All rights reserved.